Communicating at work : strategies for success in business and the professions - Adler, Ronald B. (Ronald Brian), 1946-; Elmhorst, Jeanne Marquardt; Maresh-Fuehrer, Michelle Marie; Lucas, Kristen (McGraw Hill, 2023)
"Communicating at Work provides students with strategies that are rooted in current research and real-world best practices. With Communicating at Work, students will gain the tools they need to make informed and ethical decisions in face-to-face and virtual environments and to master practical skills and competencies necessary for succeeding and maintaining balance in today's business world"--